Relative validity of three Bioelectrical Impedance Analysis equipments in measuring body composition of adults - Ghazali, Fatin Huwaina Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The aim of this study is to determine relative validity of bioelectrical impedance analysis (BIA) equipments for the measurement of body composition among adults. Three different Tanita BIA equipments namely SC 330, SC 240 and BC 545 were used to detennine body composition of participants with SC330 as the reference method. A total of 120 subjects (74 girls and 46 boys) aged 19-30 years from Universiti Sains Malaysia (USM) Kelantan took part in this study. From the study, both SC 240 and BC 545 showed significant correlation with SC 330 for body fat percentage. Specifically, in male the highest correlation \vith SC 330 for body fat percentage was SC 240 (r= 0.97, p <0.001). Meanwhile, the highest correlation ·with SC 330 for body fat percentage in female was BC 545 (r= 0.97, p <0.001). Mean body fat percentage tor SC 330 was 22.85% (SD 6.08). The mean percent body fat for SC 240 was 22.85% (SD 8.59) showed no significant difference from SC330. There was significant difference of mean body fat percentage by BC 545 to SC 330 which is 24.32% (SD 8.97). In conclusion, SC 240 shown to have good correlation \vith SC 330 and can be used as a reliable equipment in measuring body composition among adults.